(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with the logistics of the company. The article examines the growing impact of information technology for logistics protsessy.XX century was a time of very intensive development of information technologies. Domestic transport companies were among the first in the new economy have felt the need for the introduction of information technologies in the production process management. Competition in the market of transport services in connection with the emergence of many small private companies and the appreciation of the resources put transport companies faced with the need to mobilize all internal resources. The obvious is that the effective functioning of the transport companies is no longer possible without the extensive use of information technology and personal computers. This is what makes the introduction of information technologies relevant topic of transport logistics. The urgency of this problem has sparked interest from local experts. Conducted various seminars, forums, workshops, conferences, research.